Sic Semper Tyrannis the Philosophy of Law and the Right to Fight Tyranny - Kuznetsov, Michael Yurievich (UIN Sunan Gunung Djati Bandung, 2025)
This essay explores the philosophical underpinnings of the right to kill a tyrant within the framework of legal philosophy, examining its ontological, epistemological, and axiological dimensions. The discussion delineates major schools of legal philosophy—natural law (Grotius, Cicero), positive law (Aquinas, Bentham, Austin, Hart), utilitarian law (Hume, Bentham, Mill, Sidgwick), Marxist law (Marx, Engels), historical school (Montesquieu, Hugo, Savigny), sociological jurisprudence (Jhering, Gerber), and realist jurisprudence (Holmes, Llewellyn, Morgenthau)—while selectively employing all except positivist and realist approaches. Natural law, decoupled from divine origins by Grotius, prioritizes inherent human rights, whereas utilitarianism evaluates actions by their promotion of happiness, critiqued by Constant for subordinating principle to outcome. Tyrannicide evolves from class-based resistance in feudal societies to a democratic imperative in modernity, rooted in natural rights. The author laments the absence of